2016
DOI: 10.1007/s00784-016-1872-6
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist wear of monolithic zirconia crowns after 2 years

Abstract: The monolithic zirconia crowns (LAVA Plus) show acceptable antagonist wear rates after 2 years in situ, regardless of natural enamel or ceramics as antagonist materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 20 publications
7
84
0
7
Order By: Relevance
“…As expected for a composite material, the properties are intermediate between those of ceramics and particle-filled resins. 60,61,63 The elastic modulus of these materials is in the range of 30 GPa, which is half of that reported for conventional veneering ceramics but closer to what is usually reported for dentin (15)(16)(17)(18)(19)(20). 58,63 Typical ceramic materials have a higher elastic modulus values than PICN 64 .…”
Section: Polymer Infiltrated Ceramic Network (Picns)mentioning
confidence: 61%
See 1 more Smart Citation
“…As expected for a composite material, the properties are intermediate between those of ceramics and particle-filled resins. 60,61,63 The elastic modulus of these materials is in the range of 30 GPa, which is half of that reported for conventional veneering ceramics but closer to what is usually reported for dentin (15)(16)(17)(18)(19)(20). 58,63 Typical ceramic materials have a higher elastic modulus values than PICN 64 .…”
Section: Polymer Infiltrated Ceramic Network (Picns)mentioning
confidence: 61%
“…The results showed that monolithic zirconia promoted an acceptable surface wear rate of the antagonist surface (natural enamel or ceramic material) after two years. 17 Therefore, monolithic Y-TZP restorations with good surface finishing are not likely to wear significantly the antagonist element. However, following up these Y-TZP restorations is important because if there is a decrease in the surface quality, their wear potential will increase significantly.…”
Section: Monolithic Zirconia Restorationsmentioning
confidence: 99%
“…To date, there are five clinical studies which examined the wear potential of monolithic zirconia against different antagonists, including this current study (Table 1) [2527]. This table compares all clinical studies in terms of the different variables employed in each.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro studies are hard to compare with each other because of differences in surface finish of material, type of material, method of wear and type of wear analysis used. The limited clinical studies which have been published describe how monolithic zirconia is a viable restorative material in that the wear of antagonist enamel is within the range of acceptable limits [2528]. However, since there is a limited number of clinical studies available, there is need for more clinical analyses to further validate the wear compatibility of zirconia with enamel.…”
Section: Introductionmentioning
confidence: 99%
“…However, a major problem of this kind of venneered restorations, even supported with strong oxide ceramics, is their low fracture resistance and high chipping risk [3][4][5]. These problems were proposed to be solved by the recent introduction of the full-contour monolithic zirconia restorations that are veneering and glazing layer-free [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%